2002
DOI: 10.3354/ame029029
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in an aquatic microbial food web caused by inorganic nutrient addition

Abstract: Present theories regarding nutrient status of aquatic systems and plankton size structure, food web length and nutritional modes were tested in a microcosm experiment using water from the northern Baltic Sea. The different trophic levels included were those of pico-, nano-and microplankton, representing bacteria, flagellates, ciliates and diatoms. Nutrient enrichment resulted in a higher biomass and changed size-structure of the organisms. The nutrient-enriched microcosms changed from a picoplankton-dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 30 publications
4
33
0
Order By: Relevance
“…For instance, Havens (1992) demonstrated that acidification could change the parameters of freshwater plankton size spectra and Samuelsson et al (2002) show that nutrient enrichment in mesocosms resulted in higher biomass and changed plankton size structure.…”
Section: Environmental Variables Determining And/or Affectingmentioning
confidence: 99%
“…For instance, Havens (1992) demonstrated that acidification could change the parameters of freshwater plankton size spectra and Samuelsson et al (2002) show that nutrient enrichment in mesocosms resulted in higher biomass and changed plankton size structure.…”
Section: Environmental Variables Determining And/or Affectingmentioning
confidence: 99%
“…This suggests that increasing contributions of 2 to 10 µm and >10 µm size classes with increasing DIN concentrations are not due to higher growth rates. A final hypothesis is advanced by Samuelsson et al (2002) that phytoplankton develops faster in enriched conditions than mesozooplankton does. A lower predation pressure on larger cells could indeed explain this dominance of larger cells in enriched conditions.…”
Section: Phytoplankton Size Classesmentioning
confidence: 99%
“…Observations from both enclosure experiments (Joint et al 2002, Samuelsson et al 2002 and incubations of natural assemblages in seawater (Wetz & Wheeler 2003) have identified diatoms as major primary producers in bloom conditions. In addition to successful escape from grazing, diatom dominance is likely due to their capacity to exploit upwelling conditions far more effectively than other phytoplankton.…”
Section: Introductionmentioning
confidence: 99%